Saudi women in the media: Saudi and Egyptian perspectives - Abubotain, Rabaa Ahmed (AUC Knowledge Fountain, 2011)
The aim of this research is trying to differentiate between the way Saudi women see themselves as well as the Saudi males' perception of them; and the way Egyptians perceive them. Such perceptions are ignited by global media arms that have critical roles in shaping and forming opinions or pre-set ideas about Saudi woman. This research is a quantitative study in which two non probability purposive/snowball samples are selected: Egyptian and Saudi. A 400 participant of both nationalities is asked to fill a survey that is created to show the perception they have of Saudi women. Participants included are above the age of 21, highly educated and must watch TV for at least an hour per week; however, the Egyptian participants who have lived, visited Saudi a couple of times for reasons other than religious (Hajj or Omra) will be excluded to ensure that their created perceptions are neither created, enforced or changed by what they saw in real. Television viewership and exposure patterns of Saudis are different than Egyptians. Saudis follow Saudi and foreign news and never watch the Egyptian news channels, while Egyptians tend to follow Egyptian and foreign news and ignore the Saudi news channels. Saudis, on one hand, watch all the entertainment channels available when Egyptians only turn to Egyptian and foreign and never watch Saudi entertainment. When seeking information about Saudi women, Egyptians turn to foreign channels, while Saudis turn to their own local channels. Saudi participants tend to stick more to their initial source of information; whereas Egyptians tend to seek alternative sources than their initial chosen one. In general, Egyptians are considered to be a more active audience than Saudis. Participants from both countries had different perceptions of the different media. Both Saudis and Egyptians agreed that foreign media are the most credible, have the highest quality and most variety; however, they disagreed on which media are the most trusted. Saudis believe that their own Saudi media are the most trusted, while Egyptians believe that foreign media are the most trusted. Moreover, Saudis have a positive perception of their women as well as their country; however, Egyptians have a negative perception of Saudi women and Saudi Arabia. In general, participants with negative perceptions from each country had different TV watching habits. The very few Saudis with a negative perception were light viewers of TV. They never or rarely ever watch Saudi or Egyptian media and sometimes follow foreign media. However, Egyptians with negative perceptions were heavy viewers of TV. They never or rarely watched Saudi media and sometimes watch Egyptian and foreign media.